(untitled) (Web of Teachers: Inderscience Research, 2024)
Military sports training of students is a direct preparation of young people for army life. Young men must come to the army physically and mentally prepared, then they will quickly adapt to army life. In sports, a young man, and then a young man, in addition to the opportunity to improve physically, also receives spiritual skills of courage, patience, overcoming oneself, which is so necessary in modern and often quite tough life.